A prospective study of indications and maternal outcome in case of emergency obstetric hysterectomy in a tertiary care hospital of Gujarat, India - Jain, Mahima; Dave, Devanshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Obstetric hysterectomy was developed as a heroic operation arising out of necessity to control post-partum haemorrhage thereby reducing maternal mortality. The objectives of this study are to examine the incidence, indications, outcomes and complications of obstetric hysterectomy in a tertiary care hospital. It also aims to study the changing trends in incidence and indications in present day obstetric practice. Methods: This is a one-year study including 31 cases of obstetric hysterectomy performed in the Department of Obstetrics and Gynecology in a tertiary care hospital of Gujarat. Each case is analyzed, computed and tabulated as per standard proforma including clinical assessment, questionnaire, examination and investigations. Results: In present study 68% cases were in 21-30 years which is peak reproductive age. 55% patients were from rural areas and 52% cases were having three or more parity. The incidence of obstetric hysterectomy is 0.432% in both vaginal and cesarean deliveries i.e. 1 in 231 deliveries. Major indication for obstetric hysterectomy is morbidly adherent placenta 32% followed by atonic PPH 25.8% and ante partum hemorrhage in 22.58% due to increase in rate of cesarean sections. Most common complication is DIC and maternal mortality in around 16.12%. Conclusions: Obstetric hysterectomy is still a lifesaving surgery in modern day obstetrics. Quick decision for obstetric hysterectomy reduces maternal morbidity and mortality. Most of the morbidity is attributable to its indication and underlying disorder rather than the procedure itself.